Magnetization of a nonferromagnetic metal spacer sandwiched between two magnetically ordered layers - Gorobets, V.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The exchange coupling of magnetically ordered layers (MOLs) through a nonmagnetic metallic spacer was calculated. The induced magnetization in the spacer, taking into account the influence of an external magnetic field, was calculated, too. This calculation shows that the energy of coupling of the MOLs through the nonmagnetic metallic spacer is a long-periodic function of the spacer’s thickness and magnetic field, i.e., the exchange coupling between the layers varies from ferromagnetic to antiferromagnetic and vice versa depending on the spacer’s thickness and magnetic field. Also this calculation shows that in nonferromagnetic spacer the induced magnetization can undergo many complete rotations depending on distance to the boundaries with the MOLs. Moreover, absolute value of induced magnetization nonmonotonously decays with distance from the interfaces inside the spacer. It is shown that the character of the decay of absolute value magnetization from the interfaces into the interior of the spacer is influenced by magnetic field.